Vesicocutaneous fistula following inguinoscrotal hernia repair: a case report - Aninditho Dimas Kurniawan; Dahril (Journal of International Surgery and Clinical Medicine, 2021)
Introduction: A vesicocutaneous fistula (VCF) represents an abnormal association between the bladder and the skin's surface. VCF mostly present as a complication of the diseases and treatments. Maceration, difficulty in treating the infection, moisture-associated skin damage, malodor, inconveniences, and physical disability were the sign and symptoms of VCF besides the visible urine leakage. A vesicocutaneous fistula should be treated adequately when recognized due to it may give bothersome complaints, social effects, and a possibility of recurrence to the patients. Proper surgical interventions are imperative because VCF leads to life-threatening complications such as cancer and sepsis. In this case, we report a case of vesicocutaneous fistula following inguinoscrotal hernia surgical repair in a 63-years-old man in order to provide an overview of the management of patients in similar cases. Case Description A 63-years-old man with a history of strangulated hernia and underwent exploratory laparotomy and ileostomy two weeks ago. Intermittent small amounts of urine discharge from the left groin was developed eleven days after the operation. The vital sign was normal, with a physical examination revealed a wet postoperative wound at the left groin. Mild tenderness over the suprapubic area. The hematology tests were normal. Cystography with contrast revealed the contrast appears to fill the bladder, and there is neither extravasation of contrast from the bladder to the distal end of the fistulous tract. The result was confirmed as the multiple diverticles within vesica urinaria. Incision of VCF was performed, and the bladder was closed in two layers with 3-0 Chromic for the mucosa and running polyglycolic acid (vicryl) 2-0 for the muscular. Conclusion: Laparotomy should be performed with care, and the surgeon must be aware of possible organ trauma. In our patient VCF was treated by suturing the fistula after drainage.